Reseñas - Biernat, Carolina; Abad García, Emiliano; Carrillo, Gonzalo (Revista Paginas, 2016)
JEREZ, Marcelo. El problema de la vivienda en Jujuy durante los gobiernos populares (1946-1962), Editorial de la Universidad Nacional de Jujuy, San Salvador de Jujuy, 2013. GONZÁLEZ DE OLEAGA, Marisa (ed.). En primera persona. Testimonios desde la Utopía, Barcelona, NED Ediciones, 2013. HAGEMEYER, Rafael Rosa. História & Audiovisual, Belo Horizonte, Autêntica Editora, 2012.